2023
DOI: 10.3389/fpubh.2023.1142576
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to the appearance and development of burnout in nursing students: a systematic review and meta-analysis

Abstract: IntroductionBurnout may be suffered not only by experienced nurses, but also by those in training. The university environment can be highly stressful for student nurses, who are exposed to various stress-producing situations.AimThe aim of this study is to identify and analyse the main risk factors for burnout among nursing students.MethodsA systematic review with meta-analysis was performed. The search equation used was “Burnout AND Nursing students”. Quantitative primary studies on burnout in nursing students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…The findings of this study are consistent with evidence that nursing students, given the academic and clinical demands, are particularly at risk of experiencing higher levels of academic burnout. Several studies [42][43][44][45][46][47] have also reported similar results, indicating high levels of emotional exhaustion in healthcare students. All of these disparities may reflect differences in curricular structures, in the nature of professional practices, and, potentially, in the coping strategies and social support available to these students.…”
Section: Discussionmentioning
confidence: 56%
“…The findings of this study are consistent with evidence that nursing students, given the academic and clinical demands, are particularly at risk of experiencing higher levels of academic burnout. Several studies [42][43][44][45][46][47] have also reported similar results, indicating high levels of emotional exhaustion in healthcare students. All of these disparities may reflect differences in curricular structures, in the nature of professional practices, and, potentially, in the coping strategies and social support available to these students.…”
Section: Discussionmentioning
confidence: 56%
“…Work-related factors are determined by high work demands (intensity and working time), high emotional demands, lack of autonomy, poor social and labor relations, poor appreciation of their work values, and insecurity about the work situation ( 7 , 8 ). Some studies agree on the fact that factors related to the individual such as emotional instability, anxiety, and a history of depression can also influence the occurrence of burnout ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 98%
“…By examining these risk factors through empirical research and qualitative analysis, this study seeks to provide valuable insights into the dynamics of burnout in the context of final project preparation. The findings aim to inform the development of targeted interventions and support strategies that promote students' wellbeing and effectively enhance their success in completing their final projects (Velando-Soriano et al, 2023).…”
Section: Introductionmentioning
confidence: 99%